Metal‐Free Synthetic Approach to 3‐Monosubstituted Unsymmetrical 1, 2, 4, 5‐Tetrazines Useful for Bioorthogonal Reactions. (13th August 2018) - Qu, Yangyang; Sauvage, François‐Xavier; Clavier, Gilles; Miomandre, Fabien; Audebert, Pierre
Abstract: A facile, efficient and metal‐free synthetic approach to 3‐monosubstituted unsymmetrical 1, 2, 4, 5‐tetrazines is presented. Dichloromethane (DCM) is for the first time recognized as a novel reagent in the synthetic chemistry of tetrazines. Using this novel approach 11 3‐aryl/alkyl 1, 2, 4, 5‐tetrazines were prepared in excellent yields (up to 75 %). The mechanism of this new reaction, including the role of DCM in the tetrazine ring formation, has been investigated by 13 C labeling of DCM, and is also presented and discussed as well as the photophysical and electrochemical properties.